Consensus PCR and Microarray for Diagnosis of the Genus Staphylococcus, Species, and Methicillin Resistance. (December 2001) - Hamels, S.; Gala, J.-L.; Dufour, S.; Vannuffel, P.; Zammatteo, N.; Remacle, J.
We propose the use of DNA microarray for the discrimination of homologous products after a single PCR amplification with consensus primers. The method was applied to Staphylococcus identification. The femA nucleotide sequences, which are phylogenetically conserved among the staphylococci, were first amplified using a consensus primer pair together with the mecA sequence, a molecular marker for methicillin resistance. Products were then identified on a glass array. The microarray contained five selective DNA capture probes for the simultaneous and differential identification of the five most clinically relevant staphylococcal species ( S. aureus, S. epidermidis, S. haemolyticus, S. hominis, and S. saprophyticus ), while a consensus capture probe could detect all femAsequences, allowing the identification of the genus Staphylococcus . The mecAsequence hybridized to a specific capture probe. The identification was univocal because only a single capture probe had to be present for each sequence to be identified. The hybridization and identification processes were completed in less than 2 h. Current results demonstrate that low-density microarrays are powerful multigenotypic post-PCR analyzers and could compete with conventional bacteria identification.